Thyrolipoma: A Rare Thyroid Gland Entity - Singh, Pragya; Mittal, Mahesh Kumar; Sharma, Sonam (Nepalese Journal of Radiology, 2019)
Fat-containing thyroid swellings are rare with limited differentials including lipomatous goiter, heterotopic thyroid rests, amyloid goiter, lymphocytic thyroiditis, Grave’s disease, adenolipoma, intrathyroid thymic or parathyroid lipoma, encapsulated papillary carcinoma, and liposarcoma etc. We present a case of a 60-year-old euthyroid female with a long standing thyroid swelling radiologically and pathologically diagnosed as thyrolipoma (adenolipoma). Thyrolipomas are occasionally diagnosed. However, these lesions are considered to be benign and are treated surgically.